A Governance Framework for the Geospatial Information Centres (GICs) in Developing Countries إطار حوكمة مراكز المعلومات الجغرافية المكانية في البلدان النامية - Muhammad Abdulrahman Seddeek; Hossam Sami (Journal of Urban Research)
Spatial information and analysis are very beneficial for decision-makers and planners in preparing regional development plans to optimize development returns. There are numerous issues with the process of building GIC databases, especially in developing countries, mostly related to weak governance, one of which is the lack of adequate tools for gathering and arranging data; the absence of standardized information methods and recording; the inability to access this information through a working method; information preservation and recording techniques; the inability to use specialized hardware and software, etc. Egypt began creating a total of 27 GICs to cover all governorates. A questionnaire was used to learn more about the current GIC governance in four GICs, which only accept responses. It deduced that each centre has a different administrative structure and no precise exercise of good governance powers; it was evident that the GIC's governance framework was lacking. Three international GIC governance frameworks were revised, to deduce the perfect governance framework with some modifications to be more suitable for Egyptian GICs and other developing countries in order to close the gap in recent Egyptian GIC governance. The proposed framework illustrates departments and organizational structure, “which includes departments like data analysis, networks, cybersecurity, and the collection of geospatial and statistical data," human resources represented in personnel, tasks, and responsibilities, in addition to the data governance model and the controls for classifying collected data in light of data handling policies, and finally delivery channels for hardware applications and established geospatial data.